Milly, Molly and the train - Pittar, Gill; Morrell, Cris (Milly Molly Books Gisborne, N.Z., 2003)
While watching a train, Milly and Molly pick up rubbish, and find a parcel of bank notes. Includes teaching guide. Suggested level: junior